Floristic composition, diversity and economic valuation of a Coastal Hill Forest in Pulau Pangkor, Malaysia - Ghollasimood, Sholeh (2011)
The preservation of biological diversity is considered important for a variety of reasons, including economic value and preservation of natural ecosystem processes. The goal of this work was to describe all vascular plant diversity, structure, species composition along a coastal hill forest in Pulau Pangkor, Perak. The objectives were to (1) obtain trees and non-trees plant species composition and richness, and describe abundant, diverse and climbing modes of the climbers and assess plant diversity (2) calculate economic value, especially stumpage value for the forest stand and (3) estimate the biomass of trees in relation to the carbon content and energy. Five plots of one hectare each were established and each plot were divided into contiguous 100 subplots units each of 10 m×10 m quadrats. Each subplot was systematically surveyed by enumerating and identifying all vascular plants from all strata, and measuring the diameter at breast height (DBH≥5 cm) of all trees and 45 soil samples were collected to analyse soil texture. Differences of species richness and abundance between plots were analyzed by ANOVA. Diversity analysis was conducted using EstimateS (version 8.2.0) to 95% confidence intervals. A canonical correspondence analysis (CCA) was carried out to analyze the relationships between climber abundance and environmental parameters. The mean stem density was 7585 stems per ha and in total 36797 vascular plants representing 348 species belonging to 227 genera in 89 families were identified within 5-ha. The most spacious rich families were Rubiaceae having 27 species, followed by Dipterocarpaceae (21 species), Euphorbiaceae (20 species) and Palmae (14 species). Based on growth forms, 60% of all species were trees, 15% shrubs, 10% herbs, 10% lianas, 5% palms, 4% climbers, and 4% ferns. The average stumpage value was MYR 93741 per hectare. Dipterocarpaceae contributed to 86 % of the total stumpage value of the study area and the results confirmed the status of this family as the major timber species. Diversity index values including non-parametric estimators revealed that the highest level of diversity occurred with increasing number of individuals in a sample. Alpha Fisher and Shannon-Wiener from parametric and Chao 2 from non-parametric estimators were the best estimators in this study area. Species accumulation curve shows how species richness increases until eventually the curve levels off with increasing sample size and it captured a high proportion of the species richness in the third plot. Regression of elevation and palm, climber, epiphyte and shrub richness showed no significant relationship but linear regression of tree richness against altitude was significant. Although the number of trees reduced with increasing elevation, the number of trees with dbh ≥5 cm in higher altitude were increased. Climbing mechanisms differ significantly among the five plots (P<0.0001) and 52% of the climbers are adapted to this climbing mechanism. The CCA illustrates the distribution of climbers according different elevations. The CCA results explain 56% of the cumulative variance in species data, indicating that, elevation had the highest correlation with species distribution (r² = -0.4, P<0.0001; r² = -0.16, P<0.001), while soil type was not significant and showed no correlation with climber density (r² = 0.009, P≥0.85). The total above and under ground biomass of trees (dbh ≥ 5) was 665 t/ha. As half of the biomass is carbon, the estimated total carbon content is 299.4 t/ha, while the estimated energy content of all the biomass is 2.09 × 1019 KJ. In total the number of endemic species, above and below ground biomass and economy valuation, compare to the other sites of Peninsular Malaysia were high.